Novel utilisation of ultrawide-field fundus photography for detecting retinal nerve fibre layer defects in glaucomatous eyes. Issue 11 (18th May 2021) - Kim, Mi Jeung; Lee, Jung Hyun; Park, Ji In; Choi, Jin Young; Sohn, Joonhong; Hwang, Ho Sik; Hwang, Daniel Duck-Jin
Abstract : Background/aims: Evaluation of the retinal nerve fibre layer (RNFL) is important for identifying glaucomatous damage. Ultrawide-field fundus photography (UWP) imaging is increasingly used in the ophthalmological field; however, it is unknown whether it can be used for detecting RNFL defects (RNFLDs). We investigated whether RNFLD can be detected with UWP images and compared the clinical effectiveness of three types of images for detecting RNFLD: conventional red-free RNFL photography (RFP), non-mydriatic UWP and digitally converted green separation of non-mydriatic UWP (G-UWP). Methods: Eyes with glaucoma or glaucoma suspect and normal control eyes meeting the eligibility criteria were consecutively enrolled from September 2019 to April 2020. Their conventional RFP, non-mydriatic UWP and G-UWP images were assessed for detecting RNFLD to evaluate the sensitivity and specificity for detecting RNFLD. Results: Three image sets of 196 participants (84 normal control, 25 glaucoma suspect and 87 glaucoma) were obtained. The sensitivity of G-UWP (94.6%; 95% CI 88.7 to 98.0) and RFP (92.9%; 95% CI 86.4 to 96.9) was higher than that of UWP (82.1%; 95% CI 73.8 to 88.7; p<0.05). The sensitivities of G-UWP and RFP are comparable. The specificity of G-UWP (78.6%; 95% CI 68.3 to 86.8) and UWP (75.0%; 95% CI 64.4 to 83.8) was comparable, but both were lower than that of RFP (98.8%; 95% CI 93.5 to 100.0; p<0.05). Conclusion: Non-mydriatic UWP images can be used to detect RNFLD. Non-mydriatic G-UWP showed comparable sensitivity but lower specificity to conventional RFP. Non-mydriatic G-UWP could be used as a convenient and useful diagnostic tool for screening glaucoma in clinical settings.